A comparative study of the physico‐chemical properties affecting the organoleptic quality of fresh and thermally treated yellow tomato ecotype fruit. (14th December 2017) - Raiola, Assunta; Pizzolongo, Fabiana; Manzo, Nadia; Montefusco, Immacolata; Spigno, Patrizia; Romano, Raffaele; Barone, Amalia
Summary: In recent years, yellow commercial tomatoes have attracted great interest from consumers. The goal of this work was to characterise the parameters of three yellow genotypes that affect the fruit quality, in comparison with those of a red fruit genotype. Compared to the other genotypes, the GiaGiù ecotype was characterised as having the highest titratable acidity, organic acids content and pectin content before and after a thermal treatment simulating industrial pasteurisation. Most of the analysed parameters influence the taste and aroma of fresh fruit and processed products, particularly the high glutamic acid content measured in the GiaGiù ecotype. This genotype was also distinctive for its higher pectin content, which influences the texture. These features might allow the development of new food products that require a specific viscosity, such as sauces and ketchup. Interestingly, the beneficial properties of GiaGiù were preserved after thermal processing. Abstract : Physico‐chemical quality traits evaluated on fresh and thermally treated yellow tomatoes. For each evaluated trait, the significance of differences among the four genotypes analysed ( P < 0.05, Tukey's test) is reported in the graphs.